Studying the accessibility and use of digital literacy among older adults during a global pandemic - Dhesi, Simran; Heacock, Helen; McIntyre, Lorraine; Environmental Health, BCIT School of Health Sciences (BCIT Environmental Public Health Journal, 2022)
The COVID-19 global pandemic has demanded many individuals remain indoors and isolate from friends and family to keep safe. These long periods of isolation have led to loneliness and an overall shift in the way individuals communicate with each other. Digital media sources have become predominant forms of interaction and entertainment – but how are different age groups, specifically older adults managing this major digital media shift? Keywords older adult(s)